2011
DOI: 10.1016/j.bpj.2011.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Light Chain Phosphorylation and N-Terminal Extension Increase Cross-Bridge Binding and Power Output in Drosophila at In Vivo Myofilament Lattice Spacing

Abstract: The N-terminal extension and phosphorylation of the myosin regulatory light chain (RLC) independently improve Drosophila melanogaster flight performance. Here we examine the functional and structural role of the RLC in chemically skinned fibers at various thick and thin filament lattice spacings from four transgenic Drosophila lines: rescued null or control (Dmlc2(+)), truncated N-terminal extension (Dmlc2(Δ2-46)), disrupted myosin light chain kinase phosphorylation sites (Dmlc2(S66A,S67A)), and dual mutant (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 35 publications
5
31
0
Order By: Relevance
“…On the other hand, RLC phosphorylation was proposed to modify the mechanical properties of the myosin lever arm and its ability to control the step size of cardiac myosin and advancing the longer 8-nm step frequency compared with nonphosphorylated myosin (25). An RLC phosphorylation-elicited longer myosin working stroke would then lead to increased contractile force and power (26). We believe that this mechanism may underlie the pseudophosphorylation-induced prevention of the development of the D166V-HCM phenotype in transgenic S15D-D166V mice.…”
Section: Potential Mechanism Of Rescue By Pseudophosphorylation Of Mymentioning
confidence: 99%
“…On the other hand, RLC phosphorylation was proposed to modify the mechanical properties of the myosin lever arm and its ability to control the step size of cardiac myosin and advancing the longer 8-nm step frequency compared with nonphosphorylated myosin (25). An RLC phosphorylation-elicited longer myosin working stroke would then lead to increased contractile force and power (26). We believe that this mechanism may underlie the pseudophosphorylation-induced prevention of the development of the D166V-HCM phenotype in transgenic S15D-D166V mice.…”
Section: Potential Mechanism Of Rescue By Pseudophosphorylation Of Mymentioning
confidence: 99%
“…Changes to the phosphorylation level of Ser15 in ventricular RLC in the cardiac muscle affect power output in model organisms (Miller et al 2011; Scruggs and Solaro 2011). We investigated if RLC phosphorylation affects the unitary step-size/step-frequency using the Qdot assay.…”
Section: Natural Myosin Activationmentioning
confidence: 99%
“…Sweeney and colleagues showed that this disruption was due to charge repulsion between the myosin head and the thick filament, as the addition of a negative charge to the RLC mimicked this effect of phosphorylation (Sweeney et al, 1994). In terms of myosin function, the lateral displacement and/or increased mobility of the myosin head relative to the thick filament may facilitate formation of the actomyosin complex and the strongly bound, force-generating cross-bridge state in a variety of species (Levine et al, 1996;Levine et al, 1998;Miller et al, 2011;Sweeney et al, 1994). In support of this idea, Yang and colleagues showed that RLC phosphorylation effects on isometric force were mimicked by myofilament lattice spacing compression.…”
Section: Molecular Mechanism For Speed and Direction Dependencementioning
confidence: 99%